Desain Multimedia Interaktif Berbantuan Software Adobe Flash CS6 untuk Siswa Kelas V SD - Harun, Gustiayu Juita; Fitria, Yanti (Universitas Negeri Padang, 2022)
The study aims to design and determine the feasibility level of an interactive multimedia software-assisted Adobe Flash CS6 for elementary School students grade V. This type of research is research and development with the Multimedia Development Life Cycle (MDLC) method Luther-Sutopo version model through six stages, namely concept, design, material collection, assembly, testing, and distribution. Based on the stage of the development method, the result is an interactive CD in the theme of 9 subtheme 3 Learning 1, 2, and 5 with a percentage of 84.44% that meets valid criteria or deserves to be used as an interactive multimedia for students of the V grade Elementary School.